Validation of a Method for the Estimation of Food Portion Size - Fabrizio Faggiano; P. Vineis; Daniela Cravanzola; Paola Pisani; G. Xompero; Elio Ríboli; Rudolf Kaaks (1992)
In the context of the planning phase of a large cohort study on dietary habits and cancer, we have developed a food frequency questionnaire on usual food intake, which includes a set of pictures to estimate the portion size of 23 different dishes. The validity of the estimation of portion size of recently consumed foods has been questioned by other researchers. To validate the use of pictures, we organized a field trial with 103 volunteers. They were invited to a dinner where standard Italian dishes were offered (total 17 foods); all of the portions they chose were recorded and weighed. The following day, we interviewed the volunteers on what they consumed during the dinner, and we compared the weight of the food actually eaten with the weight of the food represented in the pictures. The volunteers overestimated the portion size by more than 20% for six foods and underestimated the portion size by more than 20% for four foods. In addition, we found a tendency toward overestimation of portion size by those who ate smaller portions and underestimation by those who ate larger portions ("flat slope syndrome"). (Epidemiology 1992;3:379-382)